Host ALDH2 deficiency aggravates acetaldehyde metabolism disturbance and gut microbiota dysbiosis in chronic alcohol exposure mice - Tan, Xueqin; Wu, Beiyi; Wen, Xue; Li, Yunzhu; Xu, Xuewen (Frontiers in Microbiology, 2025)
Alcohol is inextricably linked with intestinal microbiota as it was absorbed through gut. While mitochondrial aldehyde dehydrogenase 2 (ALDH2), as the major enzyme responsible for metabolizing toxic acetaldehyde to acetate, is important factor influencing alcohol metabolism. However, it is not yet known the relationship between ALDH2 knockout (KO) and gut microbiota profiles in mice under chronic alcohol exposure. Therefore, this study aimed to investigate the effect of 5% v/v alcohol exposure on the gut microbiota of ALDH2 knockout (KO-5%) and wild-type (WT-5%) mice. At the end of 10-week experiment, KO-5% mice exhibited a higher serum acetaldehyde concentration and upregulated expression of pro-inflammatory cytokines in intestine tissue than WT-5% mice. Metagenomic results revealed that the KO-5% mice had a significant decrease in alpha diversities. Moreover, KO-5% mice exhibited gut microbiota dysbiosis with the characteristic of a higher abundance of phylum Proteobacteria, and genera Stenotrophomonas and Ralstonia, whereas the level of genera Lactobacillus, unclassfied Bacilli, and Turicibacter were decreased. Additionally, genera Candidatus Arthromitus and Ralstonia were the most representatives in the KO-5% mice. Further, chronic alcohol exposure resulted in enriched expression of genes associated with bacterial metabolism and cellular processes in gut from WT mice. Taken together, our findings demonstrated a strong interaction between ALDH2 and the gut microbiota to response to alcohol exposure.